Turkish Foreign Policy to European Union and Its Chance to be a European Union Member - Minardi, Anton (Universitas Muhammadiyah Yogyakarta, 2016)
The Modern Turkish was established as a secular state whose special characteristic was brought from the Ottoman Islamic empire. The area of Turkeyâ€™s geopolitics is stretching from Asian to European continent, and always more inclined to the West. These circumstances have formed Turkish foreign policy for decades by indicating the bridging for the Asia on the East and Europe on the West with its motto â€œpeace at home, peace abroadâ€. As the secular state, Turkey recognized themselves as a country whose identity similar to the Western states given the fact that Turkish foreign policy always strive to joinÂ the European Union as their priority, as well as Turkey as a NATO member. Turkey showed a great effort through their involvement in various European affairs such as member of the Europe Council 1949, North Atlantic Treaty Organization (NATO) 1952, European Economic Community (EEC) 1959, member of the Organisation for Economic Co-operation and Development (OECD) 1961, European Community 1964, the Organization for Security and Co-operation in Europe (OSCE) in 1973, and officially applied to be member of European Union (EU) on April 14 1987. However, some obstacles remain such as the reluctance of the West toward Turkish performance in dealing with the Cyprus and Kurdish crises. This article explains how Turkish government perform its foreign policy by considering the discussion of Turkish Geopolitics, Turkish Foreign Policy, Turkey - EU Relation, Membership Issue in the EU, The Role of the U.S. to Turkish Membership in the EU, and the Chances for Turkey to be the EU member.Â Peradaban Turki modern dibentuk atas sekularitas negara dengan karakteristik khusus yang diadopsi dari kerajaan Islam Ottoman. Wilayah strategis Turki yang membentang dari benua Asia hingga Eropa telah membentuk politik luar negeri Turki selama berabad-abad dimana negara ini menempatkan diri sebagai jembatan yang menghubungkan kedua benua dengan motto â€œpeace at home, peace abroad. Meskipun demikian Politik luar negeri Turki dianggap lebih condong pada Eropa karena kesamaan identitas yang dimilikinya. Hal ini ditandai dengan keikutsertaan Turki dalam beberapa agenda internasional Uni Eropa seperti Europe Council tahun 1949, North Atlantic treaty Organization (NATO) 1952, European Economic Community (EEC) 1959, maupun agenda-agenda lainnya dan secara resmi mendaftar sebagai anggota Uni Eropa pada 14 April 1987. Akan tetapi, kebijakan Turki terhadap krisis Cyprus dan Etnis Kurdi menyebabkan kecanggungan bagi negara-negara yang tergabung dalam Uni Eropa. Tulisan ini menjelaskan politik luar negeri Pemerintah Turki terkait isu keanggotaan dalam UE serta pengaruh Amerika dalam kasus tersebut.